Mycelial growth rate and yield of oyster mushroom – Pleurotus ostreatus fruitful part (Jacquin: Fr.) Kumm at different temperatures - Turković, Samir (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2015)
In this paper are presented possibilities for production of oyster mushroom, its mycelium and compost, as well as how different temperatures affect the mycelial growth and yield of these mushrooms. Mycelium was cultivated on the PDA media, which was later transferred onto the sterilized wheat grains and at the end in the compost made from beech sawdust and hay. The ratioof sawdustandhaywas1:1.Compostcan be preparedfrom50%wheat straw +50% soybean straw, 50%wheat straw +50% corn stems, 50%wheat straw and 50% sunflower stems. The mycelium which was growing at an average temperature of 20 °Cafter 15 days was ready for the next grafting, while the mycelium, which was kept at 4 °C for the same period, had very slow growth rate. Mycelium was then inoculated onto sterile grain of wheat, which at a temperature of 20 °C grown very quickly. Two seedlings on compost were made, summer and autumn. The average air temperature during the summer seeding was 19.96 °C and in autumn 13.85 °C. It was found that the yield from the summer seeding was 17.76%, while the yield of autumn seeding was 7.2% relative to the weight of the wet substrate. Low temperatures, around 4oC have inhibitory influence on the mycelium growth and in such conditions mycelium can be stored up to one year. The average temperature of 19.96 °C is ideal for the growth of both mycelium and mushrooms, as well as the expected yield.